Declining opportunities and security employment for Israeli strategic performance (Tikrit Journal For Political Science, 2025)
The State of Israel faced many complex security challenges that required the country's leaders to articulate basic principles of national security and formulate a national security strategy that for the first time outlined responses in accordance with the founding leader of the State of Israel, David Ben-Gurion. Its legitimacy has stood the test of time, while specific responses have been adapted and modified to meet Israel's current and future challenges.
Keywords: - security. -Israel. - strategy. - transformations& threats